Transformations of the Supernatural : Problems of Representation in the Work of Daniel Defoe - Schoenenberger, Petra (Bielefeld : transcript-Verlag, 2017)
Daniel Defoe's work displays a keen interest in stories of supernatural encounters. Once considering how one might prove supernatural occurrences and whether one can trust eyewitness accounts, Defoe demonstrates that more is at stake. Like his contemporaries, Defoe wonders about the range of scientific insight, and about the moral and epistemological ramifications of unchallenged trust and faith. His transformations of the supernatural probe the boundaries of knowledge and evidence and play with the limits of cognition, emphasizing the inseparability of mind and emotion.
Frontmatter -- Contents -- 1. Introduction -- Part I: Daniel Defoe's Supernaturalism Revisited: Judgment and the Burden of Proof -- 2. Daniel Defoe's Supernatural Tracts and Contemporary Supernaturalism: Problems of Language and Evidence -- Part II: Transformations of the Supernatural: The Power of the Imagination -- 3. Defoe's Play with the "As If": Fiction, Delusion and Imagination -- 4. Describing Emotional Conflict and Continuity in Defoe's Narratives Journal of the Plague Year, Robinson Crusoe and Roxana -- Part III: Singular Experience and Collective Knowledge -- 5. Frames of Knowledge in Daniel Defoe's Story-Telling -- 6. Conclusion -- 7. Bibliography
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 16. Mai 2019)
Keywords: Supernatural in literature; British Studies; Cultural Sciences; Evidence; Fiction; Knowledge; Literary Studies; Literature; Self; Singular Experience; Supernatural; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh